The Impact of Job Training and Learning Interest on Learning Motivation and Performance in AHTC-Batu Waste Management Training - Indrarosa, Dwita; Mariyono, Joko; Santoso, Siswanto Imam; Sutaryo, Sutaryo (JESS (Journal of Education on Social Science); Vol 8 No 02 (2024): Agustus 2024, 2024)
Training is one way to improve the competence of trainees. This is certainly influenced by several factors among the interests and motivations of participants so that they can improve participant performance. This research aims to evaluate the impact of the On-the-Job Training on learning motivation. Sixty participants in the waste management program at the Animal Husbandry Training Centre(AHTC) Batu became the research sample. Primary data and survey methodology were used in this research. Path analysis is the analysis method used. Research results prove that on-the-job training and learning motivation simultaneously influence each other. On-the-job training and learning interest have a limited impact on learning motivation. Path analysis proves that the On-the-Job Training variable has a strong impact of 0.484 on Learning Motivation. Job training, learning interest, and learning motivation are proven to partially impact performance by 0.016, 0.041, and 0.042, respectively. On-the-job training, learning interest, and learning motivation all have a significant partial impact on performance. When combined, training and motivation can improve performance